Phytometabolite Dehydroleucodine induces cell cycle arrest, apoptosis, and DNA damage in human astrocytoma cells through p73/p53 regulation - Malagon Aviles, O. (2015)
Accumulating evidence supports the idea that secondary metabolites obtained from medicinal plants (phytometabolites) may be important contributors in the development of new chemotherapeutic agents to reduce the occurrence or recurrence of cancer. Our study focused on Dehydroleucodine (DhL), a sesquiterpene found in the provinces of Loja and Zamora-Chinchipe. In this study, we showed that DhL displayed cytostatic and cytotoxic activities on the human cerebral astrocytoma D384 cell line.With lactone isolated from Gynoxys verrucosa Wedd, a medicinal plant from Ecuador, we found that DhL induced cell death in D384 cells by triggering cell cycle arrest and inducing apoptosis and DNA damage.We further found that the cell death resulted in the increased expression of CDKN1A and BAX proteins. A marked induction of the levels of total TP73 and phosphorylated TP53, TP73, and ?-H2AX proteins was observed in D384 cells exposed to DhL, but no increase in total TP53 levels was detected. Overall these studies demonstrated the marked effect of DhL on the diminished survival of human astrocytoma cells through the induced expression of TP73 and phosphorylation of TP73 and TP53, suggesting their key roles in the tumor cell response to DhL treatment. © 2015 Bailon-Moscoso et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.